Vocabulary Mastery: An Analysis of 4th Grade Elementary Students Taught by Non-English Education Graduate Teacher - Anisa Nurkhasanah; Fitri Wulandari; Anggi Setiawati; Annida Istiqomah; Imam Luthfie Maajid (English Teaching and Linguistics Journal (ETLiJ), 2023)
The lack of students' ability in vocabulary makes learning English a little hampered, almost all classes experience the same thing in terms of weak mastery of vocabulary. However, especially in grade IV, vocabulary mastery is lower than the others. In mastering vocabulary in each theme, the teacher sets a minimum standard of ten mastered vocabulary. But in fact, there are still many students who do not master the ten vocabularies. Most of the difficulties in pronunciation and writing. Teacher competence is the set of knowledge, abilities and beliefs that a teacher has and displays for teaching situations. Teachers who teach not according to their field can confuse their students, apart from confusing their students, the material presented is also not detailed, or only limited to the concepts. Teachers are also considered unprofessional in teaching. This study aims to describe vocabulary learning by non-English education graduate teacher in teaching English vocabulary to fourth-grade students. This research uses descriptive qualitative with classroom observation, distributing questionnaires to students and teacher interviews as data collection techniques. Data analysis was carried out by classifying teacher interviews obtained through audio recording transcripts and student questionnaire results. The participants in this study were an English teacher and all fourth-grade students at UPT SDN 1 Tanjung Anom. The result shows that the students vocabulary is lack, because learning resource is limited, and the background of teacher is non-English education graduate teacher. The learning media used is an English dictionary book. The material taught is writing and reading. The obstacle experienced by teachers who teach English is that the teacher finds it difficult when teaching English because they are not from their major, and the learning facilities are still limited, there are no textbooks in schools.